Service Quality and Company Image on Insurance Customer Satisfaction and Loyalty - Abdul Haris; Muhammad Idris; Amirah Kallabe (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This research investigates the impact of service quality on corporate image, customer satisfaction, and customer loyalty. It was conducted at the Makassar branch of PT. General Insurance Bumiputera Muda 1967. Data were collected through a survey with a questionnaire, utilising purposive sampling to select 112 samples from the total population of 226 company customers. Structural Equation Model (SEM) was employed for data analysis. The findings indicate that service quality and corporate image significantly influence customer loyalty through their impact on customer satisfaction. Service quality emerged as the dominant factor in customer loyalty, followed by corporate image. This study highlights the pivotal role of service quality and corporate image in driving customer satisfaction and loyalty at PT. General Insurance Bumiputera Muda 1967's Makassar branch. These insights can inform strategies for enhancing customer relationships and fostering business growth.